Interrelation of Cardiological and Ophthalmological Parameters in Patients with Arterial Hypertension in Combination with Coronary Heart Disease - Jalalova Dilfuza Zukhriddinovna (Genius Publishing Group, 2022)
Hypertension is a major risk factor for cardiovascular disease and mortality, which is one of the major public health problems worldwide. Hypertension causes a number of pathophysiological ocular modifications that significantly affect the retina, choroid and optic nerve circulations, which lead to a number of ocular defects. The retina is the only site in the body where the microvascular can be directly tested, providing valuable information about hypertension associated with systemic risks. In the process of circulatory disorders in the capillaries, degeneration of the nervous tissue occurs, which is especially sensitive to any negative changes in metabolism
Keywords: Hypertension; Pathophysiological; Ocular Modifications; Retina